Business intelligence ability to enhance organizational performance and performance evaluation capabilities by improving data mining systems for competitive advantage. Issue 6 (November 2022) - Wang, Jianwen; Omar, Abdullah Hisam; Alotaibi, Fahad M.; Daradkeh, Yousef Ibrahim; Althubiti, Sara A
Highlights: Business intelligence (BI) capabilities/reliability affect performance capabilities. Artificial intelligence (AI) has an impact on Data mining systems (DMS). Integration of BI Infrastructure (BII) affects the Supply chain management. Performance evaluation capabilities has an impact on competitive advantage. BI capabilities are related to BI reliability. Thus, BII impresses BI reliability. Abstract: Improving organizational performance is a priority for the managers and experts of companies. Performance appraisal capabilities are activities that use available information to improve business processes and achieve company goals. Knowledge information entered into companies, on the one hand, is effective in learning people and, on the other hand, is used in management decisions. This study aims to improve these organizational performances by using Business intelligence (BI) and Artificial intelligence (AI) on Data mining systems (DMS) in privately held companies. This descriptive survey study is based on the purpose of applied and quantitative research. The statistical population includes managers of privately held companies. These companies use BI and AI in their data mining systems. The results revealed that BI capabilities & reliability affect performance capabilities. Further, Performance evaluation capabilities (PEC) impact competitive advantage; Since the BI capabilities are related to BI reliability, thus, Business intelligence infrastructure (BII) impresses BI reliability. Path coefficient between the two variables of integration of BII on BI capabilities is β = 0.389. Moreover, the T-statistic between these two variables is t = 5.768. Path coefficient between the two variables of BI capabilities over reliability business intelligence is β = 0.158. Moreover, the T-statistic between these two variables is t = 1.967. Path coefficient between the two variables of Integrate BII with business intelligence reliability is β = 0.344. Moreover, the T-statistic between these two variables is t = 4.452. Innovation has a significant impact on the company's performance by creating an improved market position, which indicates a competitive advantage and superior performance.